2023
DOI: 10.3389/fpsyt.2023.1102946
|View full text |Cite
|
Sign up to set email alerts
|

Sleep quality, social rhythms, and depression among people living with HIV: a path analysis based on social zeitgeber theory

Abstract: BackgroundPeople living with HIV frequently report sleep disturbances. The social zeitgeber theory, which proposes that stressful life events can interfere with sleep and even depression by destabilizing daily routines, provides new insights into identifying predictors of sleep disturbances and improving sleep in people living with HIV.ObjectiveTo explain the pathways affecting sleep quality in people living with HIV based on social zeitgeber theory.MethodsA cross-sectional study was conducted to assess sleep … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 85 publications
0
1
0
Order By: Relevance
“…Epidemiological studies have identified associations between social jetlag and the prevalence and clinical onset of diverse disorders, ranging from depression to metabolic dysfunction and reduced cognition [ 178 180 ]. Accordingly, the social zeitgeber theory proposes that disruption in the timing of daily social routines increases the risk for mood disorders and exacerbates BD [ 181 ]. Hence, social jetlag may be considered as a public health risk.…”
Section: Hallmark 5: Rhythmic Oscillationsmentioning
confidence: 99%
“…Epidemiological studies have identified associations between social jetlag and the prevalence and clinical onset of diverse disorders, ranging from depression to metabolic dysfunction and reduced cognition [ 178 180 ]. Accordingly, the social zeitgeber theory proposes that disruption in the timing of daily social routines increases the risk for mood disorders and exacerbates BD [ 181 ]. Hence, social jetlag may be considered as a public health risk.…”
Section: Hallmark 5: Rhythmic Oscillationsmentioning
confidence: 99%